Cell Membrane Penetration without Pore Formation: Chameleonic Properties of Dendrimers in Response to Hydrophobic and Hydrophilic Environments. Issue 7 (3rd June 2020) - de Luca, Sergio; Seal, Prasenjit; Parekh, Harendra S.; Tupally, Karnaker R.; Smith, Sean C.
Abstract: The mechanism by which cell‐penetrating peptides and antimicrobial peptides cross plasma membranes is unknown, as is how cell‐penetrating peptides facilitate drug delivery, mediating the transport of small molecules. Once nondisruptive and nonendocytotic pathways are excluded, pore formation is one of the proposed mechanisms, including toroidal, barrel‐stave, or carpet models. Spontaneous pores are observed in coarse‐grained simulations and less often in molecular dynamics simulations. While pores are widely assumed and inferred, there is no unambiguous experimental evidence of the existence of pores. Some recent experimental studies contradict the mechanistic picture of pore formation, however, highlighting the possibility of a direct translocation pathway that is both nondisruptive and nonendocytotic. In this work, a model is proposed a model for peptide (linear and dendritic) translocation which does not require the presence of pores and which potentially accords with such experiments. It is suggested that a charged peptide, as it experiences an increasingly hydrophobic environment within the membrane surface, can utilize a proton chain transfer mechanism to shed its protons to counter ions or potentially phospholipid head groups in the membrane skin region, thereby becoming compatible with the hydrophobic interior of the membrane. This increases the likelihood to move into the highly hydrophobic core of the membrane and ultimately reach the opposite leaflet to re‐acquire protons again, suggesting a potential "chameleon" mechanism for non‐disruptive and non‐endocytotic membrane translocation. The molecular dynamics simulations reveal stability of peptide bridges joining two membrane leaflets and demonstrate that this can facilitate cross‐membrane transport of small drug molecules. Abstract : A non‐endocytotic and non‐disruptive mechanism for membrane penetration is proposed. Charged peptides may undergo "chameleon‐like" proton shedding/reacquiring upon entering/leaving the hydrophobic membrane interior, thereby facilitating translocation. A chain transfer mechanism for this proton shedding is quantum‐chemically examined. Molecular dynamics simulations reveal stability of peptide bridges joining two membrane leaflets that can facilitate cross‐membrane transport of small drug molecules.